Quality-of-Service Routing Using Path and Power Aware Techniques in Mobile Ad Hoc Networks. (6th April 2008) - Asokan, R.; Natarajan, A. M.; Venkatesh, C.
Abstract : Mobile ad hoc network (MANET) is a collection of wireless mobile hosts dynamically forming a temporary network without the aid of any existing established infrastructure. Quality of service (QoS) is a set of service requirements that needs to be met by the network while transporting a packet stream from a source to its destination. QoS support MANETs is a challenging task due to the dynamic topology and limited resources. The main objective of this paper is to enhance the QoS routing for MANET using temporally ordered routing algorithm (TORA) with self-healing and optimized routing techniques (SHORT). SHORT improves routing optimality by monitoring routing paths continuously and redirecting the path whenever a shortcut path is available. In this paper, the performance comparison of TORA and TORA with SHORT has been analyzed using network simulator for various parameters. TORA with SHORT enhances performance of TORA in terms of throughput, packet loss, end-to-end delay, and energy.